Studi Perbandingan Kompetensi Profesional Guru Indonesia dan Thailand - Mighfar, Shokhibul; Dilfam Aldisya Ervani; Nazilatul Faizah; Anavee Khoona; Ainun Nisa (Jurnal Bintang Pendidikan Indonesia, 2024)
The quality of education is very dependent on the professional competence of teachers. This study aims to compare professional competence between teachers in Indonesia and Thailand. This research uses a qualitative approach, emphasizing comparative descriptive research. Data were collected through in-depth interviews with 6 teachers (3 from Indonesia and 3 from Thailand) representing various levels of education. Data analysis was carried out using comparative analysis. The results showed significant differences in professional competence between the two countries. Teachers in Indonesia tend to focus on mastering subject matter and implementing the national curriculum, while teachers in Thailand place more emphasis on developing interpersonal skills, classroom management skills, and the use of technology in learning. Factors that influence these differences include different education systems, educational policies, and the culture and social values of society. This research provides valuable insights for education stakeholders in both countries in designing policies and teacher training programs that meet the demands of the times. In addition, this research also contributes to further understanding of the comparison of education systems and teaching practices between Indonesia and Thailand.